PENGARUH LATIHAN FISIK DAN VIRTUAL REALITY BERBASIS GAMES TERHADAP EFIKASI DIRI PASIEN STROKE DI RSUD BLORA - Ika Puji Eviyanti; Diana Tri Lestari; Ashri Maulida Rahmawati (Yayasan Nusantara Hasana Berdikari, 2025)
Stroke is a leading cause of disability and death worldwide, including in Indonesia, impacting motor function decline and low patient self-efficacy. Conventional physical exercise is physically beneficial but is often considered monotonous, while game-based Virtual Reality (VR) offers interactive, fun, and motivating exercises. This study aims to determine the effect of a combination of physical exercise and VR on the self-efficacy of stroke patients. Self-efficacy, according to Bandura, is the belief in one's ability to complete a task. The combination of physical exercise and game-based VR is expected to provide a synergistic effect, increasing patient motivation and engagement. The research method used a quantitative quasi-experimental design with two groups: intervention (physical exercise + VR) and control (physical exercise only). The sample consisted of 35 stroke patients at Blora Regional Hospital, drawn by total sampling. The intervention was carried out for 7 days, 6 times a day, for 10 minutes per session. Self-efficacy was measured before and after the intervention using a questionnaire. Data analysis used the Wilcoxon and Mann-Whitney tests because the data were not normally distributed. The results showed that the intervention group experienced a significant increase in self-efficacy from moderate to high (p=0.001), while the control group showed no significant increase (p=0.076). Comparison between groups showed a significant difference (p=0.001), with higher scores in the intervention group. Game-based VR effectively increased self-efficacy through gradual success experiences, intrinsic motivation, and immediate feedback. Conventional physical exercise helped maintain motor function but had less impact on psychological aspects without the support of motivational stimulation. These results support the integration of VR in stroke rehabilitation programs. The combination of physical exercise and game-based VR effectively increased self-efficacy in stroke patients significantly compared to physical exercise alone. Recommendations provided include the implementation of game-based VR in nursing practice, further research with a larger sample size and intervention duration, and family support in implementing exercises to accelerate patient recovery.